Laparoscopic surgery: Any role in patients with unexplained infertility and failed in vitro fertilization cycles?. Issue 13 (March 2019) - Yu, Xiaoming; Cai, He; Guan, Jing; Zheng, Xingbang; Han, Hongjing
Abstract : Abstract: Patients who undergo several in-vitro fertilization (IVF) treatment cycles and fail to conceive present a frustrating problem to the clinician. When 1 cycle of IVF treatment fails, should we offer the couples to choose additional cycle of IVF instead of evaluation of the potential peritoneal factor? In cases of otherwise unexplained infertility, the investigation cannot be considered to be complete until laparoscopy has been performed. The aim of the study is to investigate the fertility outcome of laparoscopic treatment in infertile women with repeated IVF failures. This is a retrospective case-control study conducted in a tertiary care, academic teaching hospital from January 2012 to December 2015. Patients recruited in this study were classified into 2 groups. Study group (n = 45) were offered laparoscopy for evaluation of infertility, control group (n = 45) elected to proceed to IVF without laparoscopy. Diagnostic laparoscopy and subsequent excision of suspected endometriotic lesions, lysis of adhesion and treatment of tubal pathology were performed when indicated. Forty-four (97.8%) patients in study had pelvic pathologies and the treatment was performed at the same time. Twenty-four patients in study group conceived including 16 patients conceived spontaneously and 14 patients conceived with additional IVF following laparoscopy management. There was a significant difference in the ongoing pregnancy rates between patients conceived through IVF in study group and control group (41.9% vs 19.6%, P < .05). Laparoscopy in women with normal hysterosalpingography but recurrent IVF failures can detect unrecognized pelvic pathologies. Laparoscopy evaluation prior to additional cycle of IVF seems to improve the subsequent pregnancy rate.